2010
DOI: 10.1016/j.psyneuen.2009.08.017
|View full text |Cite
|
Sign up to set email alerts
|

What constitutes too long of a delay? Determining the cortisol awakening response (CAR) using self-report and PSG-assessed wake time

Abstract: The cortisol awakening response (CAR) is a burst of cortisol in response to awakening from sleep that is superimposed on the circadian rhythm of cortisol. Determination of the CAR is contingent on the timing of sample collection: A delay between waking and collection of the first sample may affect the rise of the CAR, and could explain equivocal findings reported in the literature. We evaluated the impact of a delay between wake time and collection of waking cortisol samples on the CAR. Two methods were used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
61
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(64 citation statements)
references
References 37 publications
3
61
0
Order By: Relevance
“…Consequently, the diurnal slope is steeper because the calculation of the diurnal slope relies on the awake 0 sample. These findings coincide with several adult studies that found a sampling delay resulted in greater awake 0 cortisol levels, regardless if measured by objective (accelerometry, polysomnograpy) or subjective measures of wake-time (Dockray et al, 2008;DeSantis et al, 2010;Okun et al, 2010).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Consequently, the diurnal slope is steeper because the calculation of the diurnal slope relies on the awake 0 sample. These findings coincide with several adult studies that found a sampling delay resulted in greater awake 0 cortisol levels, regardless if measured by objective (accelerometry, polysomnograpy) or subjective measures of wake-time (Dockray et al, 2008;DeSantis et al, 2010;Okun et al, 2010).…”
Section: Discussionsupporting
confidence: 89%
“…In these adult accelerometry studies, only 15-19% of awake 0 samples were taken without delay, whereas 82-90% were taken within 15 min of wake-time (Dockray et al, 2008;DeSantis et al, 2010). Even this short delay can be problematic as later awake 0 samples result in blunted CAR and steeper diurnal slope (Kupper et al, 2005;Dockray et al, 2008;Okun et al, 2010;Griefahn and Robens, 2011). Further, Dockray and colleagues (2008) found that when there was a delay of more than 15 min between waketime and collecting the awake 0 sample, estimates of CAR were lower than when there was delay of less than 15 min.…”
Section: Introductionmentioning
confidence: 99%
“…Although there are many studies only comparing cortisol and other physiologic parameters between two days or two work situations (Axelsson et al, 2006;Lowden et al, 2009), we recommend that future studies collect saliva samples on more days. Multiple sampling days would also help to obtain stable CAR estimates by minimizing possible sampling inaccuracies (Chida & Steptoe, 2009;Okun et al, 2010). It should be noted, however, that in the present study there were logistical difficulties in collecting saliva.…”
Section: Discussionmentioning
confidence: 87%
“…For instance, long delays (in excess of 15 min) in collecting samples within the post awakening period results in attenuated CARs (DeSantis et al, 2010;Dockray et al, 2008;Okun et al, 2010). More recently we have shown that delays as little as 5-15 minutes, previously considered tolerable, result in over-estimated CAR (Smyth et al, 2013a).…”
Section: Introductionmentioning
confidence: 83%